مدينة قلهات في المراسلات الرسمية البرتغالية (1508-1520م) دراسة وثائقية - الكيومي, سليمان بن سعيد (مجلة الشرق الأوسط للعلوم الإنسانية والثقافية, 2025)
قلهات مدينة قديمة تقع على ساحل بحر عمان، وتذكرها المصادر بأنها كانت أول عاصمة عمانية في التاريخ قبل ظهور الإسلام بعدة قرون، وقد اشتهرت كمدينة تجارية، وورد ذكرها في العديد من كتب الرحالة، مثل ابن بطوطة الذي وصفها بأنّها مركز تصدير الخيول ومنها يتم استيراد البهارات، كذلك وصفها الرحالة الإيطالي ماركو بولو في القرن الثالث عشر الميلادي في أوج ازدهارها وأطلق عليها اسم «قلاياتي، ووصفها ياقوت الحموي في كتابه معجم البلدان بقوله: مدينة بعمان على ساحل البحر إليها ترفأ أكثر سفن الهند." عندما قدم البرتغاليون للمنطقة مع مطلع القرن السادس عشر الميلادي قاموا بالسيطرة على بعض المدن العمانية الساحلية، وكانت قلهات من أوائل المواقع التي سيطروا عليها، ومنذ السيطرة البرتغالية على المدينة نجد اسم قلهات يتردد كثيرا في الوثائق والمراسلات البرتغالية، سواء في مجال التجارة أو في المجال العسكري أو غيرها من الأحداث العامة، حيث أصبحت قلهات مركز تجاريا وعسكريا للأسطول البرتغالي في الفترة من 1507- 1649م. ومن هنا تأتي هذه الدراسة من أجل تتبع ومناقشة ما دونه البرتغاليون في مراسلاتهم الرسمية حول قلهات أثناء فترة وجودهم في المنطقة، وقد صنف الباحث تلك المراسلات في مجالين ، المجال الأول هو المراسلات البرتغالية حول السيطرة على قلهات، والمجال الثاني يتعلق بالمراسلات البرتغالية الخاصة بالنشاط التجاري لمدينة قلهات في  فترة السيطرة البرتغالية. سوف تعتمد الدراسة على العديد من الوثائق البرتغالية التي تعود إلى فترة الوجود البرتغالي على سواحل عمان والخليج العربي، والتي نشرت مؤخرا في عدة مجلدات، حيث سيقوم الباحث في هذه الدراسة بفرز وتحليل الوثائق التي تطرقت إلى موضوع الدراسة، وذلك من أجل الوصول إلى صورة متكاملة عن الوضع العسكري والتجاري في قلهات في فترة السيطرة البرتغالية.
Keywords: Relations -- Oman -- Portugal; Sources -- Oman

العلاقات العُمانية اليمنية في ضوء النضال العُماني ضد الاحتلال البرتغالي خلال فترة حكم الإمام سلطان بن سيف اليعربي 1059 – 1090 هـ/ 1649 – 1679م - الجهورية, أحلام بنت حمود (دورية کان التاريخية: المستقبل الرقمي للدراسات التاريخية, 2025)
قام الإمام سلطان بن سيف اليعربي (1059-1090هـ/1649-1679م) بدورٍ مهمٍ وحاسمٍ في إنهاء الاحتلال البرتغالي على بعض أجزاء السواحل العُمانية، كما تتبع البرتغاليين في سواحل اليمن والمحيط الهندي. وكان لهذا النضال أثره على العلاقات العُمانية اليمنية؛ لاعتبارات كثيرة يأتي على رأسها الموقع الجغرافي الاستراتيجي المهم الذي تتقاسمه عُمان واليمن. وقد تزامن حكم اليعاربة في عُمان مع حكم أئمة الزيدية في اليمن عُمومًا، كما تزامن حكم الإمام سلطان بن سيف اليعربي في عُمان مع حكم الإمام المتوكل إسماعيل بن القاسم (1054-1087هـ/ 1644-1676م) في اليمن، وخلفه في حكم اليمن الإمام أحمد بن الحسن بن القاسم (1087-1092هـ/ 1676-1681م). من هذا المنطلق تهدف هذه الدراسة إلى توضيح العلاقات العُمانية اليمنية في ضوء النضال العُماني ضد الاحتلال البرتغالي خلال فترة حكم الإمام سلطان بن سيف اليعربي والإمام المتوكل إسماعيل بن القاسم الزيدي، من خلال قراءة تاريخية تحليلية في ضوء ما جاء في بعض المصادر العُمانية واليمنية. ومن خلال استقراء وثيقة تاريخية مهمة تتمثل في رسالة أُرسلت في عام 1080هـ/ 1669م، من الإمام سلطان بن سيف اليعربي إلى الإمام إسماعيل بن القاسم بن محمد، وهي بحوزة هيئة الوثائق والمحفوظات الوطنية تحت الرمز المرجعي: OM.NRAA.A.1.2.1(1)، ومقارنتها بالرسالة التي أوردها المؤرخ اليمني ابن الوزير (ت: 1147هـ/ 1734م) في كتابه: تاريخ طُبُق الحلوى وصِحاف المنّ والسلوى، والمعروف بتاريخ اليمن، وما ذكره بشأنها المؤرخ العُماني نور الدين السالمي (ت: 1332هـ/ 1913م) في كتابه: تحفة الأعيان بسيرة أهل عُمان. تتضمن الدراسة مقدمة ومبحثين وخاتمة. يركز المبحث الأول على رصد وتحليل بعض ما أوردته المصادر العُمانية واليمنية حول العلاقات بين عُمان واليمن في فترة النضال العُماني ضد الاحتلال البرتغالي. والمبحث الثاني يتناول العلاقات العُمانية اليمنية في ضوء جهود الإمام سلطان بن سيف اليعربي في إنهاء الاحتلال البرتغالي على عُمان. أما الخاتمة فتتضمن مناقشة أبرز النتائج التي توصلت إليها الدراسة.الاستشهاد المرجعي بالدراسة:أحلام بنت حمود الجهورية، "العلاقات العُمانية اليمنية في ضوء النضال العُماني ضد الاحتلال البرتغالي خلال فترة حكم الإمام سلطان بن سيف اليعربي (1059-1090هـ/1649-1679م)".- دورية كان التاريخية.- السنة الثامنة عشرة- العدد الحادي والسبعون؛ سبتمبر 2025. ص 76 – 92.
Keywords: Relations -- Oman -- Portugal; Relations -- Oman -- Yemen; Vie politique -- Oman -- 1624-1742

The Wavering Power. The Portuguese hold on the Arabian coast of Oman 1622-1650 - Costa, Daniel Filipe Ferreira da (2021)
Portuguese presence in the Gulf of Oman developed, in general, since the early sixteenth century. However, the Arab shores were constantly side-lined in favour of Hormuz, the centre of Portuguese operations in the region. That changed in 1622, when the island was lost to an Anglo-Persian force. That moment, the Portuguese chose Muscat as a regional base and, as such, the Omani world became fundamental for the consolidation and enhancement of the Portuguese position as a leading power. Yet, the rule of the Omani shores proved to be difficult and hazardous. The Estado da India’s decline in resources, increasing European competition and the rise of a new united Arab entity exacerbated those difficulties and, in a few decades, Portuguese control was reduced to Muscat itself. This study addresses some of the pivotal characteristics and events related to the Portuguese presence in the Arabian coast of Oman, from the loss of Hormuz to the fall of Muscat in 1650. Therefore, military operations, commercial undertakings, financial difficulties, political decisions, religious features and tense relations are at the centre of the narrative. This way, it would be possible to understand how the Estado da India elite in Goa and the Portuguese officials in Oman acted throughout this period. Portuguese-Omani interactions started well before 1622 and continued well beyond 1650, but the three decades addressed in this dissertation can be seen as their climax.
Keywords: Relations -- Oman -- Portugal

Documents from 1551-1879 Archivo General de Indias Arquivo Histórico de Moçambique Biblioteca Histórica de la Universidad Complutense de Madrid Biblioteca Nacional de España Instituto de Valencia de Don Juan Lily Library Real Academia de la Historia : Transcriptions, English translation, Arabic translation - Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Georg Olms Verlag, 2023)
Keywords: Relations -- Oman -- Portugal

Documents from 1551-1827 Archivo General de Indias Arquivo Histórico de Moçambique Biblioteca Histórica de la Universidad Complutense de Madrid Biblioteca Nacional de España Instituto de Valencia de Don Juan Lily Library Real Academia de la Historia : Transcriptions, English translation, Arabic translation - Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Georg Olms Verlag, 2023)
Keywords: Relations -- Oman -- Portugal

Documents from 1817-1877 Arquivo Histórico Ultramarino : Transcriptions, English translation, Arabic translation - Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Georg Olms Verlag, 2023)
Keywords: Relations -- Oman -- Portugal

Documents from 1729-1817 Arquivo Histórico Ultramarino : Transcriptions, English translation, Arabic translation - Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Georg Olms Verlag, 2023)
Keywords: Relations -- Oman -- Portugal

Documents from 1548-1912 Arquivo Diplomático do Ministério dos Negócios Estrangeiros de Portugal Arquivo Distrital de Braga Arquivo Municipal de Cascais Arquivo dos Viscondes de Vila Nova de Cerveira Biblioteca da Faculdade de Direito de Lisboa Biblioteca Geral da Universidade de Coimbra Biblioteca Municipal de Elvas Colecção Pedro Pinto Museu Nacional de Arqueologia Sociedade de Geografia de Lisboa: Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro; Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Portugal in the sea of Oman: religion and politics: research on documents, 2021)
Keywords: Relations -- Oman -- Portugal

Documents from 1611-1832 Biblioteca Nacional de Portugal (Supplement): Transcriptions, English translation, Arabic translation - Salimi, Abdulrahman al-; Jansen, Michael; Pinto, Pedro; Roy, Roopanjali; Ech-Cheikh, Mohammed; Salami, Hamid al-; Shakaili, Hilal al- (Portugal in the sea of Oman: religion and politics: research on documents, 2021)
Keywords: Relations -- Oman -- Portugal

المقاومة العربية ضد البرتغاليين في الخليج العربي خلال القرن السادس عشر - عبد العيساوي, مصلح محمد (اكليل للدراسات الانسانية, 2024)
Keywords: Relations -- Oman -- Portugal

Domination, Resistance, and Trade: The Portuguese, Oman, and Kanara on the Indian Ocean - Rao, Nagendra (Asian Review of World Histories, 2024)
Abstract Did the Portuguese always dominate the Asian powers in the sixteenth and seventeenth centuries? Colonial historians used to be confident that the West consistently dominated the East, with that domination culminating in the conquest of Asia. This paper argues that the Europeans faced significant resistance from the eastern powers, with the three-way relationship of Portugal, Kanara, and Oman examined as a case in point. The countries’ dealings with each other date to the region’s Age of Partnership, when no single power could dominate the other. In the sixteenth century, the Portuguese obtained the upper hand over the East, particularly Kanara and Oman. But in the seventeenth century, the Portuguese lost their upper hand and the Asian powers staged a resurgence. The Omanis, indeed, imitated the Portuguese by establishing factories in India. This article draws on sources such as Filmotheca Ultramarina Portuguesa, Assentos Conselho do Estado, Cartas, Patentes e Alvaras, and Documentos Remittodos India.
Keywords: Relations -- Oman -- Portugal

Portuguese - Omani relations in the years 1517-1522 - Couto, Dejanirah (12th International Conference on Ibadi Studies: Far Beyond the Atlantic: Literary Production, Exchange, and Material Culture Across Brazilian and Ibadi-Omani History, 2023)
Keywords: Relations -- Oman -- Portugal

Oman in Portuguese Epic poetry: Os Lusíadas and imperialism - Hajri, Hilal al- (12th International Conference on Ibadi Studies: Far Beyond the Atlantic: Literary Production, Exchange, and Material Culture Across Brazilian and Ibadi-Omani History, 2023)
Keywords: Relations -- Oman -- Portugal

The Principles of Islamic Maritime Law in the Indian Ocean before the Advent of the Portuguese - Khalilieh, Hassan S. (12th International Conference on Ibadi Studies: Far Beyond the Atlantic: Literary Production, Exchange, and Material Culture Across Brazilian and Ibadi-Omani History, 2023)
Keywords: Relations -- Oman -- Portugal

The Estado strikes back: Oman and the Realignment of Portuguese Presence in the Gulf 1610-1624 - Teles E Cunha, João (12th International Conference on Ibadi Studies: Far Beyond the Atlantic: Literary Production, Exchange, and Material Culture Across Brazilian and Ibadi-Omani History, 2023)
Keywords: Relations -- Oman -- Portugal

Portugal in the Sea of Oman: religion and politics. Research on documents (Georg Olms Verlag, 2021)
Keywords: Relations -- Oman -- Portugal

Muscat and the Portuguese: economic and political dynamics in the early 16th century (1507-1529) - Couto, Dejanirah (Arabian Humanities, 2022)
Based on recently published literature, this article examines the relationship between Oman’s coastal towns and the Portuguese in the early decades of the 16th century. He takes as an example the port of Muscat, whose remarkable natural conditions had favored, from medieval times, its supremacy as a bridgehead for the hinterland regions and leader of the commercial networks of the West Indian Ocean, to the detriment of other Omani ports. This superiority, which also rest on its ability to orient its economy on several fronts, was reinforced by the presence of the Portuguese, who, following their attack in 1507, appointed Muscat as a stopover of their fleets and established there a factory. In addition, the progressive involvement of the Portuguese in the economic life of Muscat was accompanied by a growing political interference in the internal affairs of the city, symbolized by an implication in the conflicts which opposed the urban elites of Muscat to those of the other cities of Oman and also to Hormuz, which, while exercising its authority over the towns on the Omani side, had become, after the double conquest of Afonso de Albuquerque (1507 and 1515), protectorate of the Portuguese.
Keywords: Relations -- Oman -- Portugal